93 Sexually Transmitted Infections Remain Under-Diagnosed and Under-Treated in Young Men Presenting with Acute Scrotal Pain. (4th May 2021) - Thomas, M; Thursby, H; Kitchen, M; Liu, S
Abstract: Introduction: Epididymitis or epididymo-orchitis causing acute scrotal pain in men ≤35 years is a common presentation to primary and secondary care.Most are caused by sexually-transmitted-infections in this age group. Failure to identify or treat STIs in this population may lead to subfertility.We assessed our practice against British Association of Sexual Health and HIV guidelines. Method: Men (age ≤35) diagnosed at our centre with epididymitis/epidiymo-orchitis between January2015 and January2020 were included (n = 313, age range 16-35). Data collected included microbiological and radiological reports, antimicrobial treatment prescribed and documentation of appropriate advice and follow-up.Patients with previous STI were excluded. Results: 53 (16.9%) patients had mid-stream urine analysed;one identified bacterial growth (e.coli).15/313 patients were screened for c.trachomatis.228 (72.8%) patients had a scrotal ultrasound;167 (73.2%) reports suggested epididymitis.32 patients underwent immediate scrotal exploration;19 were epididymitis, one required orchidectomy. Advice to attend GU-Medicine-clinic was documented in 48cases (15.3%).20 patients (6.4%) received optimal antibiotic management; 83 (26.5%) received suitable antibiotics assuming non-gonococcal cause.210 patients received inadequate/inappropriate antibiotics. Conclusions: Management of patients with acute scrotal pain is sub-optimal;most patients were inadequately investigated and most received inappropriate antibiotics which may lead to subfertility.Better education and written patient information on risks of STIs may improve outcomes in this population.